Evaluation of eggplant accessions based on their quantitative and qualitative traits performance under tropical climate - Datta, Debi Rani; Rafii Azizah, Mohd Y.; Mashitah, Misran; Oladosu, Jusoh; Md. Azadul, Yusuff; Mohammed, Haque; Jatto, Itopa (Plant Archives, 2023)
Agro-morphological genetic variation on yield and yield-related traits plays an important role in varietal development in eggplant. The present study assessed different genetic variations of 27 eggplant accessions using yield and yield- related morphological traits. The experiment was laid out in a randomized complete block design with three replications. All collected data on nine qualitative and eleven quantitative traits were subjected to analysis of variance using SAS 9.4 software, while variance components were estimated. All the studied traits (quantitative) exhibited high significant variation (p ‰ 0.01). The quantitative traits such as number of primary branches per plant, fruit diameter, fruit length, fruit girth, average fruit weight, number of fruits per plant, fruit length to width ratio, and fruit yield per plant can be exploited through selection as these traits have high PCV, GCV, h2B and GAM. Considering diversity patterns and other agronomic traits, the accessions BB1 from group I, accessions BT13, BM9, BB26, BB31, BM5 from group II, BB23 from group III, BT17 from group IV, BB12 and BT6 from group V and BT15 from group VI was taken into consideration as better parents for an effective hybridization program.